Pre-swelling of FAA3 membranes with water-based ethylene glycol solution to minimize dimensional changes after assembly into a water electrolyser: Effect on properties and performance - 말리카 나지바; Kong, Jimin; Khalid, Hamza; Jarom？r Hn？t; Park, Hyun S.; Bouzek, Karel; Henkensmeier, Dirk (Elsevier BV, 2023)
Stability of membranes in electrolysers is challenged by dimensional changes, when dry membranes are assembled and wetted when the electrolyser starts. Assembling wet membranes is challenging because water evaporates during handling. To minimize dimensional changes, FAA3 membranes are pre-swollen in aqueous ethylene glycol (EG, boiling point 197？C). Membranes partially dissolve in 100 vol% EG, and swell excessively in 70 vol%. Swelling in 50 vol% shows smallest dimensional changes during handling (shrink) and re-immersion in KOH solution (swelling, mimicking start of the electrolyser). These membranes show about 30% higher conductivity (ca. 65 mS cm？ 1). Tensile strength and Young’s Modulus decrease exponentially with the amount of absorbed EG solution, while elongation at break increases. In addition to the improved dimensional stability during handling, EG treated membranes perform better in the electrolyser than untreated membranes. In a stability test over 120 h at 250 mA/cm2 , all membranes show an initial drop in the cell voltage and then stabilize.